The Influence of Police Related Media, Victimization, and Satisfaction on African American College Students' Perceptions of Police - Franklin, Andrew Sheldon; Perkins, Robert Kelvin; Kirby, Morgan D.; Richmond, Kijana P. (Frontiers in Sociology, 2019)
This study explored the roles of police related television programming, and satisfaction with most recent police contact in predicting perceptions of law enforcement performance and treatment of minorities for students with no police victimization experiences. The current study also explored the role of personal and familial police victimization experiences impact on perceptions of police. A convenience sample of 246 African American students (168 females and 78 males) ranging in age from 17 to 59 (Mage = 21.73), attending a historically Black university completed a questionnaire assessing demographic information, satisfaction with most recent contact with police, personal and familial police victimization experiences, and law enforcement related television programming. Results showed that African American students with personal and familial police victimization experiences had significantly different perceptions of law enforcement than individuals with no victimization experiences or just familial victimization experiences. Results also highlighted the predictive power of crime reality shows, police excessive force media consumption, and satisfaction with police in influencing perceptions of police. These significant relationships and causal models may be salient for understanding pertinent factors that influence perceptions of law enforcement in African American college students.